Retrospective Study of Ligature Material on Suicidal Hanging - Akhter, Syeda Sharmina; Salim, Airin; Hossain, Mohammad Monir; Uddin Razib, SM Jashim; Karmakar, Pijush (Eastern Medical College Journal, 2022)
Background: Hanging is one of the most common methods of suicide. It is always suicidal unless otherwise proved. Recent evidence showed that the incidence of suicide by hanging has increased especially among young adults. Ligature material plays an important role in leading investigation in hanging. The ligature material depends on its accessibility and availability. Various ligature materials are being used like nylon rope, cotton rope, wire, synthetic saree, lungi etc. Objective: Present study is a humble effort to find out the choice of ligature material used by the victim at Dhaka Medical College. Materials and methods: A retrospective study was conducted at the mortuary of Forensic medicine department, Dhaka Medical College Hospital, Dhaka, Bangladesh from July 2017 to December 2018. During this period data were collected from 112 cases of medicolegal autopsies by purposive sampling. Result: A total of 112 medicolegal autopsies were analyzed. In this hanging death, the most common ligature material used was rope in 58% of cases followed by dupatta (13%), lungi (11%) and saree (9%). Electric wire and kamiz were other ligature material used for hanging. The consistency of ligature material observed was hard (71%) & width is narrow width is (71%). Majority of cases (71%) were observed is male. Complete hanging was seen in 67% of cases & among them 85% cases are atypical hanging. Conclusion: Hanging is always suicidal unless otherwise proved. It is the form of painless violent asphyxia death that is widely practiced method of suicide. The most used ligature material is rope. Rope is chosen as ligature material due to its availability and accessibility. Young people in the justice system may need personal and psychological support to reduce the incidence of suicide. Eastern Med Coll J. Jan 2023; 8 (1) 12-14